Diffusion-Weighted MRI for the Assessment of Liver Fibrosis: Principles and Applications. - Palmucci, Stefano; Cappello, Giuseppina; Attinà, Giancarlo; Fuccio Sanzà, Giovanni; Foti, Pietro Valerio; Ettorre, Giovanni Carlo; Milone, Pietro (BioMed Research International, 2015)
The importance of an early identification of hepatic fibrosis has been emphasized, in order to start therapy and obtain fibrosis regression. Biopsy is the gold-standard method for the assessment of liver fibrosis in chronic liver diseases, but it is limited by complications, interobserver variability, and sampling errors. Several noninvasive methods have been recently introduced into clinical routine, in order to detect liver fibrosis early. One of the most diffuse approaches is represented by diffusion-weighted liver MRI. In this review, the main technical principles are briefly reported in order to explain the rationale for clinical applications. In addition, roles of apparent diffusion coefficient, intravoxel incoherent motion, and relative apparent diffusion coefficient are also reported, showing their advantages and limits.